SAR arc observation during the overlap registration of an energetic plasma with a plasmapause aboard the Van Allen Probe. (1st November 2020) - Ievenko, I.B.
Abstract: Stable auroral red (SAR) arcs are the consequence of interaction of the outer plasmasphere (plasmapause) with energetic ions of the ring current. In this work the event of SAR arc observation using the all-sky imager (ASI) at the Yakutsk meridian (130°E; 200°E, geom.) simultaneously with the registration of plasmapause and energetic ion fluxes aboard the Van Allen Probe B satellite at the beginning of the large magnetic storm on March 17, 2015 (St. Patrick's Day geomagnetic storm) is presented. ASI registers the intense SAR arc at the 52-59°N geomagnetic latitudes in the MLT evening sector from the observation start at 1116 UT (1926 MLT) during the low auroral activity at IMF Bz > 0. The Probe B determines the plasmapause location in the L 3–4 interval and registers the inner boundary of the H + and O + energetic ion fluxes at L 2.8–3.3 near the meridian of optical observations. The DMSP- F19 satellite registers the electron temperature subauroral peaks (Te peak) at 1014 and 1155 UT in the evening MLT sector. We show that SAR arc in this event maps the overlap region of plasmasphere dusk-bulge by the energetic ions flux of the ring current after the onset of magnetic storm. Highlights: SAR arc observation due to the ring current overlap with the plasmapause is presented. Polarward edge of arc maps the plasmasphere boundary in the dusk-bulge sector. Equatorward edge of arc maps the inner boundary of the energetic ions flux. The energetic ions O + flux significantly exceeds the energetic protons flux.